The Interplay between Hepcidin, Il-6, and NF-ΚB in Transfusion-Dependent Thalassemia-Β Patients - Assha Luthfianie Alifah; Lantip Rujito; Wahyu Siswandari (Indonesian Journal of Global Health Research, 2025)
Hepcidin, a key regulator of iron metabolism, interacts with inflammatory cytokines like IL-6 and transcription factors such as NF-κB, which play crucial roles in the body's response to inflammation and iron homeostasis especially in transfusion-dependent Thalassemia-β patient. Their interplay in transfusion-dependent thalassemia-β patients, particularly in the context of iron chelation therapy, remains underexplored. Understanding these dynamics could provide insights into optimizing treatment strategies for better patient outcomes. Objective: Determine the relationship between hepcidin levels and IL-6 and NFκB in β-thalassemia sufferers who underwent blood transfusions and determine the effect of the type of iron chelation, and the regularity of iron chelation consumption with the relationship between hepcidin, IL-6 and NFκB levels in β-thalassemia sufferers who underwent transfusions blood. Method: A cross-sectional, quantitative correlation study involving transfusion-dependent thalassemia-β patients was conducted. Serum levels of hepcidin, IL-6, and NF-κB were measured, and the relationships among these biomarkers were analyzed using Pearson correlation. The impact of iron chelation therapy type and adherence on these relationships was also assessed using stratified statistical analysis. Results: Hepcidin levels with IL-6 were found with p = 0.757. The next analysis is the relationship between Hepcidin levels and NFκB with p = 0.029. Conclusions: The relationship between hepcidin levels and IL-6 did not contribute significantly, while there was a significant relationship between hepcidin levels and NFκB. The relationship was influenced by moderating variables, namely the type of iron chelation and the regularity of iron chelation consumption.